Rasgos para um teatro comum - Mota, Levy Galvão (2020)
This research reflects on the theater as a particular political instance of human relations, especially concerning the possibility offered by the theatrical event to the sharing of the common, of the idea of community, drawing from theoretical references in both theatre studies and political philosophy, such as Chantal Mouffe, Giorgio Agamben, Hannah Arendt, Jean-Luc Nancy, Judith Butler, Jorge Dubatti and Denis Guenoun. The encyclopedic gesture of this work, organized along twelve entries, or “scratches”, have no intention of operating definitive conceptualizations. On the contrary, it merely points to ways, opening slits of thought, toward an experimental methodology based on the College de France seminars How to live together, by Roland Barthes. Thus, this dissertation does not propose the invention of a new form of theater, but instead highlights the theater’s character of political praxis and its possibilities of action in contemporary times.